Frequencies Analysis on Suling Te’dek using Fast Fourier Transform: Ethnic Musical Analysis - Lantana Dioren Rumpa; Martina Pineng; Irvan Phare; Herman Kandari (TEKNOLOGI DITERAPKAN DAN JURNAL SAINS KOMPUTER, 2023)
The aim of this research was to use the Fast Fourier Transform (FFT) to analyze the frequency of notes produced by the traditional Te'dek flute of the Toraja people in South Sulawesi, Indonesia. The purpose of the study was to contribute to the preservation of the Toraja's cultural history by providing an evaluation of the Te'dek flute's tonal characteristics. The research process included recording the sound of the flute, applying the FFT to the recorded data to extract frequency values, and analyzing these values to determine the frequency of each note within an octave. What sets the Te'dek flute apart is its unique tuning process, where the maker skillfully adjusts the fingerholes' diameter using hand tools and relies on intuition to determine the sound without any external measurement. The results of the study showed that the FFT can be used to accurately determine the frequency of the Te'dek flute and that the strength of airflow in the flute's cavity plays a significant role in determining the frequency of the tone.